Roles of mitochondrial dynamics modulators in cardiac ischaemia/reperfusion injury - Chayodom Maneechote (2018)
© 2017 The Authors. Journal of Cellular and Molecular Medicine published by John Wiley & Sons Ltd and Foundation for Cellular and Molecular Medicine. The current therapeutic strategy for the management of acute myocardial infarction (AMI) is to return blood flow into the occluded coronary artery of the heart, a process defined as reperfusion. However, reperfusion itself can increase mortality rates in AMI patients because of cardiac tissue damage and dysfunction, which is termed ‘ischaemia/reperfusion (I/R) injury’. Mitochondria play an important role in myocardial I/R injury as disturbance of mitochondrial dynamics, especially excessive mitochondrial fission, is a predominant cause of cardiac dysfunction. Therefore, pharmacological intervention and therapeutic strategies which modulate the mitochondrial dynamics balance during I/R injury could exert great beneficial effects to the I/R heart. This review comprehensively summarizes and discusses the effects of mitochondrial fission inhibitors as well as mitochondrial fusion promoters on cardiac and mitochondrial function during myocardial I/R injury. The comparison of the effects of both compounds given at different time-points during the course of I/R injury (i.e. prior to ischaemia, during ischaemia and at the reperfusion period) are also summarized and discussed. Finally, this review also details important information which may contribute to clinical practices using these drugs to improve the quality of life in AMI patients.